Effects of wind-rain coupling on the aerodynamic characteristics of a high-speed train. Issue 231 (December 2022) - Yu, Mengge; Sheng, Xugao; Liu, Jiali; Huo, Wei; Li, Meixiang
Abstract: Simultaneous effect of crosswind and rainfall on railway vehicles has raised concern lately as it threatens the operational safety. In this study, the wind-rain coupling effects on the train aerodynamics have been systematically investigated by means of Euler-Lagrangian approach. The aerodynamic computational model is established based on non-spherical raindrops, and model verification is conducted with the aid of existing measurement results. The flow features as well as the train aerodynamic coefficients under wind-rain environments are systematically studied. The results show that, the mass concentration of raindrops around a train increases with rainfall intensity. The aerodynamic coefficients show linear relationship with the increase of rainfall intensity. Unlike that of a crosswind condition, train aerodynamic coefficients exposed to combined wind and rain are dependent not only on train shape and yaw angles, but also on resultant wind velocity and rainfall intensity. The formulae for predicting the aerodynamic coefficients of the train operating in wind-rain environments are finally obtained in this paper. Highlights: The wind-rain combined effect on the high-speed train is investigated using Euler-Lagrangian approach. The aerodynamic behaviour of the high-speed train is compared between wind-rain condition and pure crosswind condition. The yaw angle, resultant wind velocity and rainfall intensity are factors affect the aerodynamic coefficients. Explicit equations for predicting train aerodynamic coefficients exposed to wind-rain conditions are finally obtained.